Magnetic‐Field‐Induced Dielectric Anomaly and Electric Polarization in Co4Ta2O9. Issue 7 (19th May 2015) - Fang, Yong; Yan, Shiming; Zhang, Lei; Han, Zhida; Qian, Bin; Wang, Dunhui; Du, Youwei; Raveau, B.
<x xml:space="preserve">Abstract</x> We report magnetic and electric properties of Co4Ta2O9, which is a collinear antiferromagnet with trigonal structure. At zero magnetic fields, no dielectric anomaly and electric polarization are observed in this compound. While, finite dielectric peaks and electric polarization develop under applied magnetic field, and increase with increasing field, showing magnetodielectric and magnetoelectric performance. We ascribe the magnetic‐field‐induced dielectric anomaly and electric polarization in Co4Ta2O9 to spin fluctuation and domain effect.